2004
DOI: 10.1634/stemcells.22-5-675
|View full text |Cite
|
Sign up to set email alerts
|

Study of Telomere Length Reveals Rapid Aging of Human Marrow Stromal Cells following In Vitro Expansion

Abstract: Human marrow stromal cells (MSCs) can be isolated from bone marrow and differentiate into multiple tissues in vitro and in vivo. These properties make them promising tools in cell and gene therapy. The lack of a specific MSC marker and the low frequency of MSCs in bone marrow necessitate their isolation by in vitro expansion prior to clinical use. This may severely reduce MSC proliferative capacity to the point that the residual proliferative potential is insufficient to maintain long-term tissue regeneration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
520
6
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 697 publications
(568 citation statements)
references
References 37 publications
(73 reference statements)
35
520
6
7
Order By: Relevance
“…To detect lipid vacuoles, cultures were stained for oil red O as described previously. (17) A well was considered positive if it contained more than 20 cells with red lipid vacuoles. The number of CFU-A was calculated following the Poisson distribution and using the formula F o ¼ e Àx , where F o is the fraction of colony-negative wells, e is a constant whose value is 2.71, and x is the number of colony-forming units per well.…”
Section: Colony-forming Unit-adipocyte (Cfu-a)mentioning
confidence: 99%
“…To detect lipid vacuoles, cultures were stained for oil red O as described previously. (17) A well was considered positive if it contained more than 20 cells with red lipid vacuoles. The number of CFU-A was calculated following the Poisson distribution and using the formula F o ¼ e Àx , where F o is the fraction of colony-negative wells, e is a constant whose value is 2.71, and x is the number of colony-forming units per well.…”
Section: Colony-forming Unit-adipocyte (Cfu-a)mentioning
confidence: 99%
“…Bone marrow‐derived mesenchymal stem cells (BMMSCs) decline in number with aging and show degenerative properties including reduced osteogenic differentiation capacity, increased adipogenic differentiation capacity and reduced proliferative ability; these are partially caused by bone aging (Wilson et al., 2010; Zhou et al., 2008). Different mechanisms of MSC senescence have been demonstrated including telomere shortening (Baxter et al., 2004), increased reactive oxygen species (ROS) (Stolzing & Scutt, 2006) and transcriptional control (Li et al., 2017). However, the complex molecular network is still largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The differences in expandability may be explained by telomere length and telomerase activity (20)(21)(22), although some studies have indicated that telomerase activity does not occur in MSCs during expansion (23).…”
mentioning
confidence: 99%